Simulation of a 3-stage propane refrigeration cycle and analysis the effect of varying compressor pressure ratio on the overall energy consumption - Abdul Halim, Abdul Hamid (2023)
In this research, propane as an energy source that can be obtained through various methods naturally such as petroleum process is used as working fluid inside liquefaction of natural gas process. Propane is known to be one of the best substances to produce the least carbon dioxide emission into the atmosphere through related industrial usage such as oil and gas processes by observing its Global Warming Potential (GWP) value. However, a normal cryogenic process for natural gases requires massive amounts of energy due to the compressor power requirement generally. The power requirement can be manipulated through the compressor ratio. Hence, it is important to examine the best condition of the compressor to produce the desired quality for Liquefied Natural Gas (LNG) and safe for environmental aspects. Aspen HYSYS V.12 is the main software to recreate the simulation of liquefaction for natural gas through a 3-stage propane pre-cooled mixed refrigerant (C3MR) process. The compressor power usage will be observed, and the compressor pressure ratio is manipulated. The data is validated by comparing the compressor power produced from another journal to imitate the condition similarity for specific plant capacity of the process. Briefly concluding this research, the increase of pressure in every compression stage will result in lower energy consumption.